1999
DOI: 10.1017/s0890037x00045000
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate Injury, Rainfastness, Absorption, and Translocation in Purple Nutsedge (Cyperus rotundus)

Abstract: Greenhouse and laboratory experiments were conducted to study activity, rainfastness, absorption, and translocation of glyphosate with and without a nonionic organosilicone surfactant in purple nutsedge. Purple nutsedge responded differently to glyphosate depending on growth stage. Glyphosate at 2.24 kg ai/ha in 17-d-old and at 4.48 kg/ha in 10-wk-old plants controlled purple nutsedge at least 96%. Regrowth of plants and tuber resprouting were greatly reduced in these treatments. Organosilicone surfactant did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 22 publications
4
34
0
8
Order By: Relevance
“…Bryson (1988), estudando o efeito de intervalos sem chuva no controle de plantas novas de Sorghum halepense, observou que os herbicidas ácido-fosfonados (glyphosate e SC-0224) precisaram de períodos bem superiores aos exigidos pelos herbicidas seletivos estudados. Segundo Bariuan et al (1999), a absorção de C 14 -glyphosate sal isopropilamina aumentou de 2,84% uma hora após a aplicação para 4,18; 6,42; 8,35; e 21,39%, respectivamente 6, 24, 72 e 168 horas após aplicação de Roundup Ultra (560 g ha -1 do produto comercial) em Cyperus rotundus.…”
Section: (A) (B)unclassified
“…Bryson (1988), estudando o efeito de intervalos sem chuva no controle de plantas novas de Sorghum halepense, observou que os herbicidas ácido-fosfonados (glyphosate e SC-0224) precisaram de períodos bem superiores aos exigidos pelos herbicidas seletivos estudados. Segundo Bariuan et al (1999), a absorção de C 14 -glyphosate sal isopropilamina aumentou de 2,84% uma hora após a aplicação para 4,18; 6,42; 8,35; e 21,39%, respectivamente 6, 24, 72 e 168 horas após aplicação de Roundup Ultra (560 g ha -1 do produto comercial) em Cyperus rotundus.…”
Section: (A) (B)unclassified
“…For example, glyphosate activity was reduced by ª80% when rainfall occurred within 4 h of treatment (Bryson 1987;Bovey et al 1990). Similarly, glyphosate efficacy was reduced by one half and one third when simulated rainfall occurred at 1 h and 24 h, respectively, after glyphosate application compared with no rain (Bariuan et al 1999). The loss of glyphosate activity due to rainfall was prevented when the rain-free period was extended to 72 h. Feng et al (2000) found that the efficient uptake of Roundup was correlated with rainfastness.…”
Section: Introductionmentioning
confidence: 99%
“…The Engame formulation has increased efficacy over formu-and growth stage under evaluation (Roggenbuck et al 1990;Reddy & Singh 1992) and the type of formulation (Feng et al 2000) also were factors affecting surfactant efficacy in improving control with glyphosate. Surfactant efficacy in increasing weed control with glyphosate was also dependent on the duration of the rain-free period (Bryson 1987;Bovey et al 1990;Reddy & Singh 1992;Bariuan et al 1999). Adjuvant effectiveness might also vary with pH.…”
Section: Introductionmentioning
confidence: 99%
“…Bariuan et al (1999) mostraram que o glyphosate só não diminui sua afetividade no controle de Cyperus rotundus se o período sem chuva após a aplicação for de 72 horas. Bryson (1988) constatou que o glyphosate necessitou de um período mínimo de quatro horas sem chuvas após a aplicação para que não houvesse redução na sua eficácia.…”
Section: Silvaunclassified